Approximation of solutions of boundary value problems for integro-differential equations of the neutral type using a spline function method - Ihor Cherevko; Andrii Dorosh; Ivan Haiuk; Andrii Pertsov (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
Boundary value problems for nonlinear integro-differential equations of the neutral type are investigated. A scheme for approximating the boundary value problem solution using cubic splines of defect two is proposed and substantiated. A model example illustrating the proposed approximation scheme is considered.